1997
DOI: 10.1021/jo962007y
|View full text |Cite
|
Sign up to set email alerts
|

α-Vinylation of 1,3-Dicarbonyl Compounds with Alkenyl(aryl)iodonium Tetrafluoroborates:  Effects of Substituents on the Aromatic Ring and of Radical Inhibitors

Abstract: Direct alpha-vinylations of enolate anions derived from 1,3-dicarbonyl compounds with 4-tert-butyl-1-cyclohexenyl(aryl)iodonium 2 and 1-cyclopentenyl(aryl)iodonium tetrafluoroborates 3 are reported. Frequently, alpha-phenylations compete with the vinylations in the reaction of 1,3-dicarbonyl compounds with alkenyl(phenyl)iodonium salts 2a and 3a. Use of alkenyl(p-methoxyphenyl)iodonium salts 2b and 3b, however, leads to selective alpha-vinylation at the expense of the competing arylation of 1,3-dicarbonyl comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 70 publications
0
32
0
4
Order By: Relevance
“…The reactivity of this novel compound class was subsequently investigated and compared to known reactivity of acyclic vinyliodonium salts. Ochiai and co‐workers reported the vinylation of nitrocyclohexane with cyclohexenyl(aryl)iodonium tetrafluoroborates, which delivered a mixture of vinylated and arylated nitrocyclohexanes (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of this novel compound class was subsequently investigated and compared to known reactivity of acyclic vinyliodonium salts. Ochiai and co‐workers reported the vinylation of nitrocyclohexane with cyclohexenyl(aryl)iodonium tetrafluoroborates, which delivered a mixture of vinylated and arylated nitrocyclohexanes (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…Vinylbenziodoxolone 6 a and the corresponding styryl(phenyl)iodonium salt 7 were submitted to Ochiai's conditions, as detailed in Table . Reactions with the vinyl(phenyl)iodonium salt 7 delivered a product mixture with vinylated product 8 as the major product, together with minor amounts of the terminal alkene 9 and the phenylated product 10 (entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that, compared to the reaction of alkenyl(phenyl)-λ 3 -iodane 9, use of alkenyl-λ 3 -iodane 10 with p-methoxyphenyl group as a carbon ligand on the iodine(III) tends to increase the selectivity for α-vinylation of 1,3-dicarbonyl compounds at the expense of the competing α-arylation. 8 Thus, the presence of an electron-releasing para methoxy group decelerates the nucleophilic aromatic substitution at the ipso position. Similar electronic effects of substituents in determining selectivity were reported in the nucleophilic ipso substitution of unsymmetrical diaryl-λ 3 -iodanes.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, enolate anions derived from various 1,3-dicarbonyl compounds can be vinylated with cyclohexenyl ( 410 ) and cyclopentenyl iodonium salts to afford products 411 (Scheme 136). 798…”
Section: Iodine(iii) Compoundsmentioning
confidence: 99%